2017
DOI: 10.3389/fphar.2017.00330
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine for the Management of Glycemic Control and Clinical Outcomes of Type 1 Diabetes Mellitus: A Systematic Review and Meta-Analysis of Randomized Controlled Studies

Abstract: Importance: Telemedicine has been shown to be an efficient and effective means of providing care to patients with chronic disease especially in remote and undeserved regions, by improving access to care and reduce healthcare cost. However, the evidence surrounding its applicability in type 1 diabetes remains scarce and conflicting.Objective: To synthesize evidence and quantify the effectiveness of telemedicine interventions for the management of glycemic and clinical outcomes in type 1 diabetes patients, relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
141
3
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(150 citation statements)
references
References 42 publications
4
141
3
2
Order By: Relevance
“…We found that if the QoL benefits were to persist over a lifetime, there would be a gain of 0.95 QALYs. The life-time base-case, subgroup, and sensitivity CEAs were all consistent with each other (eTables [11][12][13][14].…”
Section: Discussionsupporting
confidence: 61%
“…We found that if the QoL benefits were to persist over a lifetime, there would be a gain of 0.95 QALYs. The life-time base-case, subgroup, and sensitivity CEAs were all consistent with each other (eTables [11][12][13][14].…”
Section: Discussionsupporting
confidence: 61%
“…Telemedicine has the potential to help reduce disparities in diabetes management especially in remote regions, by improving access to care and reducing health care costs as demonstrated in this study of older adults . While a recent meta‐analysis found a mean reduction in HbA1c of 0.18% with use of telemedicine, given the paucity of data available and heterogeneity of the studies included in the analysis, the findings are limited . When impact of telemedicine was investigated by subpopulation, its use was noted to be successful in adolescents with a mean difference in HbA1c of −0.32% between groups .…”
Section: Telehealthmentioning
confidence: 86%
“…296 Importantly, those studies with longer duration (>6 months) and those that recruited individuals with higher baseline HbA1c values (≥9%) demonstrated greater benefit. 296 Thus, a cautious optimism can be used when considering application of this technology in the future.…”
Section: Adoption Of Telemedicine Into Clinical Practicementioning
confidence: 99%
“…A recent meta‐analysis of 13 randomized controlled trials including 4207 adults with T1D found that telemedicine was associated with a significant decline in HbA1c compared with usual care . However, findings among pediatric patients with T1D have been more equivocal, and no studies so far have included separate subgroup analyses of younger children and adolescents . This pilot study was conducted to assess the impact of a 6‐month intensive remote therapy (IRT) intervention for children and adolescents with T1D.…”
Section: Introductionmentioning
confidence: 99%
“…17 However, findings among pediatric patients with T1D have been more equivocal, and no studies so far have included separate subgroup analyses of younger children and adolescents. 18,19 This pilot study was conducted to assess the impact of a 6-month intensive remote therapy (IRT) intervention for children and adolescents with T1D. We hypothesized that real-time collection of data regarding insulin, blood glucose, and physical activity, in conjunction with rigorous outreach, would improve glucose control among these patients.…”
Section: Introductionmentioning
confidence: 99%